First detection of radon progeny recoil tracks by MIMAC. (30th June 2017) - Riffard, Q.; Santos, D.; Guillaudin, O.; Bosson, G.; Bourrion, O.; Bouvier, J.; Descombes, T.; Fourel, C.; Muraz, J.-F.; Lebreton, L.; Maire, D.; Colas, P.; et al.
Abstract: The MIMAC experiment is a μ-TPC project for directional dark matter search. Directional detection strategy is based on the measurement of the WIMP flux anisotropy due to the solar system motion with respect to the dark matter halo. The main purpose of MIMAC project is the measurement of nuclear recoil energy and 3D direction from the WIMP elastic scattering on target nuclei. Since June 2012 a bi-chamber prototype is operating at the Modane underground laboratory. In this paper, we report the first ionization energy and 3D track observations of NRs produced by the radon progeny. This measurement shows the capability of the MIMAC detector and opens the possibility to explore the low energy recoil directionality signature.